An Evaluation of Healthy Eating Scale for Patients with Pre-Diabetes Using Rasch Analysis - Kerry Anne de Vent; Nguyen Hoang Nguyen Do; Fakir M. Amirul Islam (Applied Sciences, 2023)
Consumption of a healthy diet is required to manage blood glucose level in people with diabetes or pre-diabetes. The aim of this study was to test the internal validity of healthy eating habits assessed using a self-reported scale, the Rapid Eating Assessment for Participants (REAP) scale, in participants with pre-diabetes. The scale had 15 items with 4 categories: “Never”, “Rarely”, “Some days” and “Usually/most days”. Those items were administered to 119 participants from 2006 to 2008 in Victoria, Australia. Rasch analysis was applied using RUMM2030 software. Overall fit was adequate in the unaltered model (χ2 = 29.29, p = 0.500, person separation index (PSI) = 0.500), however, seven items had disordered thresholds which were remedied by collapsing “Rarely” with “Some days” (χ2 = 37.36, p = 0.166, psi = 0.550). Item 1 (“Eat 3 main meals”) remained disordered after collapsing. Two persons were removed due to their fit residuals being outside ±2.5, however, these deletions did not improve the fit, so it was decided to retain these persons in the scale. Overall, there was no significant differential item functioning (DIF) or local dependency. However, there was evidence of multidimensionality and a ceiling effect toward healthy eating in the person item threshold. The results from Rasch analysis showed that the current scale needs some improvement, such as addressing disordered thresholds, for measuring eating habits for people with pre-diabetes. A modified version with middle categories collapsed would provide a psychometrically more robust measure. Further study is needed to validate the scale as a screening tool for measuring healthy eating among people with pre-diabetes.